Safety of anesthesia for children with mucopolysaccharidoses: A retrospective analysis of 54 patients. Issue 5 (23rd April 2018) - Scaravilli, Vittorio; Zanella, Alberto; Ciceri, Valentina; Bosatra, Mariagrazia; Flandoli, Claudia; La Bruna, Alessia; Sosio, Simone; Parini, Rossella; Gasperini, Serena; Pesenti, Antonio; Moretto, Alessandra
Summary: Background: Complications are common during anesthesia for patients with mucopolysaccharidoses. San Gerardo Hospital (Italy) is a reference center for mucopolysaccharidoses with a dedicated pediatric anesthesia service. Aims: This study aims to evaluate the safety of anesthesia for mucopolysaccharidoses patients, describe their anesthetic management at our institution, and assess risk factors for complications. Methods: The anesthetic charts of mucopolysaccharidoses patients admitted from January 1999 to December 2014 were retrospectively analyzed. We retrieved patients' demographics; location and type of the procedure; anesthetic approach airway management and occurrence of difficult intubation and complications and outcome at hospital discharge. A generalized linear mixed model was performed to assess risk factors for complications and difficult intubation. Results: Fifty‐four consecutive children were included. The anesthetic charts of 232 procedures (52% radio‐diagnostics, 15% orthopedics, 15% ear‐nose‐throat surgery, 10% neurosurgery, and 8% general surgery) were analyzed. Each patient underwent a median of 4 (1‐6) procedures. The median age at the first procedure was 2 (1‐5), and overall age was 5 (2‐8) years old. One hundred and twenty‐five (54%) procedures were performed in remote locations. General anesthesia was utilized for 100 (43%) procedures. No death was recorded. Twenty‐one (9%) procedures had respiratory complications. Remote location anesthesia was associated with increased risk for complications (odds ratio 5.405 [1.355‐28.571], P = .016). All planned intubations (n = 65) were successful. Nineteen (29%) of those were defined difficult. All emergency intubations (n = 3) failed and were rescued by laryngeal mask airways. Older age was associated with an increased risk of difficult intubation (OR 1.200 [1.019‐1.436], P = .028). Conclusion: Patients with mucopolysaccharidoses are at high risk for anesthesia‐related complications. Remote location anesthesia is associated with increased risk for complications, and older age is associated with increased risk for difficult intubation.